From Noise to Bruit in Organization Communication: Roaming with French Knowledge/Theory - Ahmad, Che Mahzan (International Digital Organization for Scientific Information, 2014)
Noise is a problem in organization communication that moves along Anglo-Saxon configurations of knowledge. In that system, inspired by the received doctrine of Shannon and Weaver model of communication, noise must be excluded in and from a relationship. In French knowledge/theory, noise is a bruit. At the hand of Serres, bruit becomes an energy of interference and difference to the system via various morphing, bruit = parasite = Venusian third (wo) man = joker. The new knowledge landscape is possible via anti-method as a way about. Anti-method rejects the two cultures paradigm. For Serres the traditional methodology promotes closure, repetition and predictability. As a method that invents, anti-method pivotal axis is mixtures (metissage). In this engagement, one is mixing with circum-tances of the past and the present, culture and sciences, concepts and data, subjects and objects through connective intellection action. Randonnee, an exodic wanderings based upon non-linear dynamical system, is compulsory before one is able to harvest new meanings and energy. Practically, organization communication practitioners as intellectual operators must adhere to the grammar of Hermes and the grammar of the educated third as architectonic of organizing. With French knowledge/theory, organization communication is moving from the old pleats and folds of old knowledge into a third living where operators no longer feel the same wind, same waves or the same shores as before.